The KM Times They Are A-Changin’ - Meliha Handzic (Journal of Entrepreneurship, Management and Innovation)

(untitled)
This paper traces the changes in the development of the field of knowledge management (KM) over time, through a review of the representative literature and the author’s own research. The paper starts by going back to the origins of KM and reflects on three significant evolutionary stages termed fragmentation, integration and fusion. Following these reflections on the KM past, the paper speculates on the possible KM future. It identifies three emerging trends named extension, specialization and reconceptualization that point to several possible KM futures. The first two involve decentralisation and regeneration of prior KM interpretations, while the third trend signals a revolutionary next KM generation. Irrespective of the direction it may take, the evidence presented in this paper suggests that KM has a future, although it may not be without challenges.